Personalized therapy based on sequential molecular analysis leads to 30 months of survival in a patient with diffuse unresectable gastric linitis plastica. Issue 6 (December 2018) - Mahjoubi, Linda; Cecchi, Fabiola; Massard, Christophe; Calabro, Fabio; Gazzah, Anas; Bahleda, Rastislav; Jamme, Philippe; Gelli, Maximiliano; Goere, Diane; Lacroix, Ludovic; Adam, Julien; Heukamp, Lukas; et al.
Introduction: Diffuse gastric cancer is associated with poor prognosis. We report a patient with metastatic gastric linitis plastica harboring human epidermal growth factor receptor 2 ( HER2 ) activating mutation and HER2 amplification. Case description: The patient received 5-fluorouracil/folinic acid and oxaliplatin combined with trastuzumab/pertuzumab, resulting in disease control for 8 months. Second-line therapy with nivolumab and trastuzumab/pertuzumab was well-tolerated, with macroscopic peritoneal response. Following ovarian progression and surgical resection of ovarian metastases, immunohistochemistry of PD-L1 was negative; proteomics demonstrated normal expression of HER2 and absence of PD-L1, while genomics showed HER2 amplification, suggesting mechanisms of escape to dual HER2 blockade by downregulation of HER2 and to nivolumab by the absence of PD-L1. Based upon this and nonexpression of biomarkers of taxane resistance, therapy was changed to paclitaxel. Two and a half years after diagnosis, the patient is undergoing treatment, with excellent performance status. Conclusions: Molecular analysis and personalized therapy can help optimize treatment in difficult-to-treat cancers.